The Effect of Learning Plan Innovation on Students' Cognitive Outcomes At School MIS Darul Ikhlas Lubuk Pakam - Rossy Annisa; Alicia Syabina; Citra Utami; Jihan Andini; Wisda Naura; Nuha Mu’adzah Rana; Siti Ismahani (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of the learning process is to achieve the goals set for the educational process. To understand the threshold of students' ability to accept subject matter, one can look at student performance in class, which is completely unrelated to student motivation and teacher creativity in presenting material. Thus, the teacher's duty is to continuously improve the quality of teaching. Innovative classroom learning is a classroom teaching strategy that encourages sharing of class materials with students. These materials include expository, inquiry, problem-based learning, improving thinking skills, cooperative learning, contextual learning, affective learning, and scientific approaches. The aim is to convey the importance of educational planning in relation to educational activities. This study uses qualitative methods with interview data collection techniques. The results of research on the relationship between the effect of lesson planning and learning activities show that there is a significant difference between the two. Using lesson plans during the teaching process can help increase student scores in the teaching process.